2020
DOI: 10.1177/1545968320929681
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Balance Adaptability and Retention in People With Multiple Sclerosis: A Systematic Review and Meta-Analysis

Abstract: Aim. To compare reactive balance in people with multiple sclerosis (MS) with healthy controls and to examine the ability of people with MS to adapt their reactive balance and retain training effects. Data Sources. Electronic databases (PubMed, EMBASE, PsychINFO) and reference lists of included articles from inception to February 25, 2019. Study Selection. Case-control and intervention studies that assessed reactive balance using mechanical perturbations in people with a confirmed diagnosis of MS. Results. Meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…To date, PBT has been studied primarily in healthy community-dwelling older adults. However, there is also emerging evidence for the effectiveness of PBT in ‘high risk' older adults (for example assisted living residents, or older adults with a history of falls or balance problems), and people with Parkinson's disease, stroke and multiple sclerosis ( 121 123 , 156 , 158 , 159 , 172 176 ). PBT trials have also been conducted in people with chronic obstructive pulmonary disorder ( 152 ) and incomplete spinal cord injury ( 165 ), but due to limited findings will not be discussed in detail in this article.…”
Section: Implementation In Practicementioning
confidence: 99%
“…To date, PBT has been studied primarily in healthy community-dwelling older adults. However, there is also emerging evidence for the effectiveness of PBT in ‘high risk' older adults (for example assisted living residents, or older adults with a history of falls or balance problems), and people with Parkinson's disease, stroke and multiple sclerosis ( 121 123 , 156 , 158 , 159 , 172 176 ). PBT trials have also been conducted in people with chronic obstructive pulmonary disorder ( 152 ) and incomplete spinal cord injury ( 165 ), but due to limited findings will not be discussed in detail in this article.…”
Section: Implementation In Practicementioning
confidence: 99%
“…A recent meta-analysis has shown that pwMS have worse reactive balance compared to healthy controls across a range of measures (eg, shorter reactive step, more recovery steps needed), which might be caused by a considerably longer response time to initiate balance recovery. 43 Critically, the meta-analysis also indicated that adaptability of reactive balance is still intact in pwMS, mainly via improved “feedforward” mechanisms (ie, using prior knowledge to predict and fine tune motor commands).…”
Section: Solutionmentioning
confidence: 99%
“…Regarding fall prevention, agility seems to be critical, as situations predisposing a fall never occur pre-planned. In this context “perception-action coupling,” (ie, feedback mechanisms 43 ) might be as important to evade a fall, as it is to evade a defender in football. It has been shown that kinematic and kinetic variables differ when comparing planned versus unplanned side-stepping, suggesting different motor control strategies when reacting to a stimulus.…”
Section: Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed and inappropriate generation of corrective forces from the postural muscles may result in falling and injuries [ 3 ]. Reactive balance control is supported by visual, vestibular, or somatosensory feedback, and it can be improved by repeated exposure to perturbations not only in healthy young and older adults, but individuals with neurological diseases, such as multiple sclerosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%